The emerging role of small extracellular vesicles in saliva and gingival crevicular fluid as diagnostics for periodontitis. (13th November 2021) - Han, Pingping; Bartold, Peter Mark; Ivanovski, Sašo
Abstract: Periodontitis is a highly prevalent multifactorial chronic inflammatory disease associated with a destructive host immune‐inflammatory response to microbial dysbiosis. Current clinical diagnosis is reliant on measuring past periodontal tissue loss, with a lack of molecular biomarkers to accurately diagnose periodontitis activity in 'real‐time'. Thus, discovery of new classes of diagnostic biomarkers is of critical importance in periodontology. Small extracellular vesicles (<200 nm in diameter; sEVs) from oral biofluids (saliva and gingival crevicular fluid—GCF) are lipid‐encapsulated bilayered vesicles and have recently emerged as a potential source of biomarkers for periodontal disease (gingivitis and periodontitis), due to the cargo of protein, genetic material and lipids derived from their parent cells. There is limited information on the isolation and characterisation methods of saliva/GCF‐sEVs or the characterisation of sEVs cargo as biomarkers for periodontitis. In this review, we detail the composition of sEVs and summarise their isolation and characterisation from saliva and GCF. The potential role of saliva and GCF‐derived sEVs in periodontitis diagnosis is also explored. It is proposed that sEVs cargo, including protein, microRNA, message RNA and DNA methylation, are potential biomarkers for periodontitis with good diagnostic power (area under the curve—AUC > 0.9).